2016
DOI: 10.15406/jnsk.2016.04.00123
|View full text |Cite
|
Sign up to set email alerts
|

The Role of BDNF Gene Polymorphism in Formation of Clinical Characteristics of Migraine

Abstract: Objective: There is evidence that brain-derived neurotrophic factor (BDNF) has a role in migraine pathophysiology. In our research, association of substitutions in BDNF gene (rs6265, rs11030107, rs2049046) with clinical parameters of migraine is considered. Background: Brain-derived neurotrophic factor (BDNF) is a neurotrophin presented widely in central nervous system. BDNF regulates axonal growth and differentiation; synapse formation; activity of dopaminergic, serotoninergic, GABA-ergic, and cholinergic neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…After exclusion of 54 hits for not meeting the inclusion criteria, five studies with 1,442 cases and 1,880 controls were, therefore, included in the final meta-analysis (1821, 25). The detailed flowchart of literature review process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After exclusion of 54 hits for not meeting the inclusion criteria, five studies with 1,442 cases and 1,880 controls were, therefore, included in the final meta-analysis (1821, 25). The detailed flowchart of literature review process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Methodological items for quality assessment and individual item scores of each included study are illustrated in Table 2. Three studies were classified as “higher” quality studies (1921), while the remaining two studies were rated as “lower” quality studies (18, 25). Genotypic data for the BDNF gene rs6265 were available in four studies as subgroups of migraine with and without aura (18, 20, 21, 25).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations